Harnessing reactive oxygen/nitrogen species and inflammation: Nanodrugs for liver injury. (January 2022) - Liu, Min; Huang, Qiong; Zhu, Yan; Chen, Li; Li, Yumei; Gong, Zhicheng; Ai, Kelong
Abstract: Overall, 12% of the global population (800 million) suffers from liver disease, which causes 2 million deaths every year. Liver injury involving characteristic reactive oxygen/nitrogen species (RONS) and inflammation plays a key role in progression of liver disease. As a key metabolic organ of the human body, the liver is susceptible to injury from various sources, including COVID-19 infection. Owing to unique structural features and functions of the liver, most current antioxidants and anti-inflammatory drugs are limited against liver injury. However, the characteristics of the liver could be utilized in the development of nanodrugs to achieve specific enrichment in the liver and consequently targeted treatment. Nanodrugs have shown significant potential in eliminating RONS and regulating inflammation, presenting an attractive therapeutic tool for liver disease through controlling liver injury. Therefore, the main aim of the current review is to provide a comprehensive summary of the latest developments contributing to our understanding of the mechanisms underlying nanodrugs in the treatment of liver injury via harnessing RONS and inflammation. Meanwhile, the prospects of nanodrugs for liver injury therapy are systematically discussed, which provides a sound platform for novel therapeutic insights and inspiration for design of nanodrugs to treat liver disease. Graphical abstract: The scope and focus of this article. RONS overproduction and inflammation are the major features of multiple types of liver injury, with known crosstalk between RONS and inflammation. Nanoparticles with RONS-scavenging or inflammation-regulating function could ameliorate liver injury through eliminating RONS and inhibiting inflammation. These therapeutic nanodrugs used for treatment of liver disease are divided into three categories according to structure and mechanism of action. Image 1 Highlights: RONS and inflammation play an essential role in the liver injury progression. The development of nanodrugs harnessing RONS and inflammation is expected to achieve superior efficacy for liver injury. Nanodrugs that scavenging RONS and inhibiting inflammation are systematically reviewed.